Sustainable Knowledge Management and Firm Innovativeness: The Contingent Role of Innovative Culture - Abang Azlan, Mohamad; T., Ramayah; Lo, May Chiun (MDPI, 2020)
This study presents the moderating effect of innovative culture on the relationship between knowledge management and firm innovativeness. The consequences of organisations that do not practice innovative culture would result in their inability to respond and react effectively to changes in the dynamic nature of the business environment and henceforth unable to achieve superior performance. In attempting to answer the research questions, a total of 202 MSC Malaysia organisations took part in the survey. To assess the developed model, WarpPLS (version 7.0) was applied based on path modelling and then bootstrapping. The results highlighted that three of the four dimensions of knowledge management, namely knowledge acquisition, knowledge application and knowledge protection were positively and significantly related to firm innovativeness. On the other hand, innovative culture was found to moderate the relationships between knowledge acquisition and firm innovativeness; and knowledge application and firm innovativeness.